2022
DOI: 10.1101/2022.05.13.491792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Galectin-9 interacts with Vamp-3 to regulate cytokine secretion in dendritic cells

Abstract: Intracellular vesicle transport is essential to maintain cellular homeostasis and is known to be mediated by the endosomal pathway and SNARE proteins. Endosomal-mediated transport to the plasma membrane ensures cytokine secretion in dendritic cells (DCs) and the initiation of effector immune responses. Despite the critical importance of this process, the specific molecular agents that regulate DC cytokine secretion are poorly characterised. Galectin-9, a ß-galactoside-binding protein, has emerged as novel modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
1
5
1
Order By: Relevance
“…Illustrating its versatility, galectin-9 was first characterised as an eosinophil chemo-attractant 23 , it induces cell death and immune tolerance by binding T cell immunoglobulin-3 in T helper 1 (TH1) cells 24 , it promotes the expansion of immunosuppressive macrophages 25 and monocytic myeloid-derived suppressor cells 26 and it has been shown to negatively regulate B cell receptor signalling 27,28 . Contrary to these reports implicating an immunosuppressive role for galectin-9, we and others have previously identified galectin-9 to positively regulate DC biology although many of its functions in myeloid cells remain poorly defined [29][30][31] .…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Illustrating its versatility, galectin-9 was first characterised as an eosinophil chemo-attractant 23 , it induces cell death and immune tolerance by binding T cell immunoglobulin-3 in T helper 1 (TH1) cells 24 , it promotes the expansion of immunosuppressive macrophages 25 and monocytic myeloid-derived suppressor cells 26 and it has been shown to negatively regulate B cell receptor signalling 27,28 . Contrary to these reports implicating an immunosuppressive role for galectin-9, we and others have previously identified galectin-9 to positively regulate DC biology although many of its functions in myeloid cells remain poorly defined [29][30][31] .…”
Section: Introductioncontrasting
confidence: 99%
“…We next set to unravel the molecular mechanisms by which membrane-bound galectin-9 modulates RhoA activity at the cytosol thereby regulating actin polymerisation and contractility in DCs. The transmembrane adhesion protein CD44 has been shown to interact with galectin-9 in T cells and Natural Killer cells 48,49 and we identified CD44 to be an interacting galectin-9 binding partner in moDCs 29 . Furthermore, CD44 interacts with RhoA via its cytoplasmic tail and its spatial organisation is determined by the dynamic remodelling of the actin cytoskeleton.…”
Section: Galectin-9 Controls Rhoa-mediated Contractility In Dendritic...mentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, it was recently reported that galectin-9 facilitates the trafficking of cytokines to the cell surface in dendritic cells. Galectin-9 depletion resulted in the accumulation of cytokine-containing vesicles in the Golgi complex that eventually underwent lysosomal degradation [ 116 ].…”
Section: Indirect Relationship Between Galectins and Cytokinesmentioning
confidence: 99%
“…For example, in the cytoplasm galectin-1 dimers can directly interact with Raf-effectors which subsequently improves H-Ras nanoclustering in the membrane [ 30 ]. Recently, galectin-9 was suggested to interact with VAMP-3 in order to control cytokine trafficking in dendritic cells [ 31 ]. Haudek et al provided an extensive overview of the intracellular binding partners of galectin-3, which includes nuclear proteins involved in splicing [ 32 ].…”
Section: The Galectin Protein Familymentioning
confidence: 99%